Ultrasound Guided Intravenous Access by Nursing versus Resident Staff in a Community Based Teaching Hospital: A “Noninferiority” Trial - Carter, Thomas; Conrad, Chris; Wilson, J. Link; Dogbey, Godwin (Emergency Medicine International, 2015)
Objectives. Ultrasound (US) guidance is a safe and effective method for peripheral intravenous (IV) catheter placement. However, no studies have directly compared the success rate of emergency medicine (EM) residents and nurses at using this technique especially in community hospital settings. This prospective “noninferiority” study sought to demonstrate that nursing staff are at least as successful as EM residents at placing US guided IVs. Methods. A group of 5 EM residents and 11 nurse volunteers with at least two years’ experience underwent training sessions in hands-on practice and didactic instruction with prospective follow-up. Two failed attempts on a patient using standard approach by an emergency department (ED) nurse were deemed to be “difficult sticks” and randomly assigned to either a nurse or resident, based on the day they presented. Results. A total of 90 attempts, consisting of trials on 90 patients, were recorded with a success rate of 85% and 86% for residents and nurses, respectively. With a p value of .305, there was no statistically significant difference in the success rate between the residents and nurses. Conclusion. Properly trained nursing staff can be as equally successful as EM residents in placing US guided intravenous lines.